Visual Codes Generated through Urban Art. Cultural Confluences between Colombia and Mexico - Mellink-Méndez Sialia Karina; Monzón-Larios Ernesto; Amado-García Jesús Alberto; Suarez-Reyes Mayerly Andrea (SHS Web of Conferences)
In recent years, artistic manifestations have had a greater impact on the economic, cultural and social axes. The objective of this research is to examine the visual codes generated through the urban art of Bucaramanga, Santander, Colombia and Ensenada, Baja California, Mexico. Two case studies were selected with themes aligned with the Sustainable Development Objectives. In Bucaramanga, the case is “Community Tourism”, a program to transform forgotten and in some cases violated spaces in the city, where through street art: murals and graffiti, neighborhoods and different corridors of the urban area are given new meaning. As far as Ensenada is concerned, it is La Colectiva Maremoto, who generates urban interventions to make gender inequality visible and promote a future in which women and non-binary gender participate in safer environments. The scope is descriptive, to account for codes, visual techniques and discursive lines used in Latin American artistic expressions. It is concluded that although urban artists are immersed in the orange economy, it is relevant to appropriate the needs and approaches of other economies, as in the cases shown here, purple and green economies, since with their capacity for mass communication they generate spaces for reflection and promote social well-being.